Retracted: Novel spiro‐thiazolidin‐4‐one and thioether derivatives of benzylidene flavanones: New leads in cancer and microbial chemotherapy. Issue 5 (12th March 2018) - Mukhtar, Sayeed; Alsharif, Meshari A.; Alahmdi, Mohammed I.; Parveen, Humaira; Khan, Asad U.
Retraction: The above article from Archiv der Pharmazie, published online on 12 March 2018 in Wiley Online Library (wileyonlinelibrary.com ), has been retracted by agreement between the authors, the journal Editor‐in‐Chief, Prof. Holger Stark, and Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim. The retraction has been agreed due to errors in the spectroscopic data of the investigated new compounds. Reference to Retraction: S. Mukhtar, M. A. Alsharif, M. I. Alahmdi, H. Parveen, A. U. Khan, Arch. Pharm. Chem. Life Sci . 2018;1–12. DOI: 10.1002/ardp.201700397